Hepatoprotective activity of dried and fermented processed virgin coconut oil. - Zakaria, Zainul Amiruddin; Rofiee, M. S.; Somchit, Muhammad Nazrul; Ahmad, Zuraini; Sulaiman, Mohd Roslan; Teh, Lay Kek; Salleh, M. Z.; Long, Kamariah (Hindawi Publishing Corporation, 2011)
The present study aims to determine the hepatoprotective effect of MARDI-produced virgin coconut oils, prepared by dried- or fermented-processed methods, using the paracetamol-induced liver damage in rats. Liver injury induced by 3 g/kg paracetamol increased the liver weight per 100 g bodyweight indicating liver damage. Histological observation also confirms liver damage indicated by the presence of inflammations and necrosis on the respective liver section. Interestingly, pretreatment of the rats with 10, but not 1 and 5, mL/kg of both VCOs significantly (